Why is fiscal policy often procyclical? - Alberto Alesina; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2005)
Many countries, especially developing ones, follow procyclical fiscal policies, namely spending goes up (taxes go down) in booms and spending goes down (taxes go up) in recessions. We provide an explanation for this suboptimal fiscal policy based upon political distortions and incentives for less-than-benevolent government to appropriate rents. Voters have incentives similar to the "starving the Leviathan" classic argument, and demand more public goods or fewer taxes to prevent governments from appropriating rents when the economy is doing well. We test this argument against more traditional explanations based purely on borrowing constraints, with a reasonable amount of success.
Keywords: H6; H3; 330; Finanzpolitik; Konjunktur; Public Choice; Wahlverhalten; Korruption; Theorie; OECD-Staaten; Entwicklungsländer